Quasiclassical trajectory study of six-centered bond exchange reaction between hydrogen molecules - Ibrahim Ali , Noorbatcha (Institut Kimia Malaysia (IKM), 1998)
The termolecular reaction between three hydrogen molecules is modelled as occurring between a dimer (H2)2 and a hydrogen molecule. The potential energy for these system is calculated on the basis of London-Eyring-Polanyi-Sato approach by adjusting the Sato parameter to reproduce the ab initio energy barrier of 69 kcal/mol for the six centered transition state involving the three hydrogen molecules. The dynamics of this reaction is studied using the quasi-classical trajectory approach. We find that the six-centered bond exchange reaction between the three hydrogen molecules do take place but with low reaction probability at translational energies much higher than anticipated on the basis of ab initio calculations. The preferred mechanism is found to be the bond exchange between the incoming molecule and one of the diatomic molecule in the dimer. The other molecule in the dimer merely acts as an anchor rather than actually taking part in the bond formation or breaking process. The detailed analysis of the trajectories reveal that these reactions have significant level of stereo-selectivity due to the planarity requirement of the six-centered transition state. The rate of enhancement of the reactivity due to the vibrational energy of the reactants is found to be similar to that of the translational energy.